IMPLEMENTASI KEBIJAKAN DANA DESA DI DESA KARAVE KECAMATAN BULUTABA KABUPATEN MAMUJU UTARA - Kamaruddin, Muh. (Katalogis, 2018)
This study aimed: to determine and to analyze the implementation of Village Fund Policy at Karave Village Bulutaba District North Mamuju Regency. This study used the theory of van Metter and van Horn, stating six indicators of policy implementation, namely (1) Policy standards and targets, (2) Resources, (3) Interagency relationship, (4) Characteristics of implementing agencies, (5) Disposition, and (6) Conditions of social, political, and economical environment. The research method used was qualitative, and the informants were determined purposively deemed to understand the problems studied, they were Head of Village Governance Division of North Mamuju Board for Community and Village Governance Empowerment, Head of Karave Village, Secretary of Karave Village, Speaker of Karave Village Consultative Body, and Public Figures of Karave Village. Types of data used were primary and secondary data. Data were collected through observation, interviews, and documentation. The results showed that (1) the Policy standards and targets could be concluded that it had been fulfilled marked by the of priority determination process of public needs before conducting Village Fund Policy. (2) Resources: the implementing staff were critically incompetent and lacking ability and skill in the implementation of Village Fund Policy resulting in unoptimal management of Village Fund. (3) Communication and implementing activities: uncommitted implementers in communication and coordination with related parties resulted in unoptimal implementation of Village Fund Policy. (4) Characteristics: the implementing agencies were not cooperative in the program implementation, resulting in unoptimal implementation of Village Fund Policy. (6) The indicator of economical, social, and political environmental conditions was unmet due to the existence of actors or community and community groups who rejected Village Fund Policy because they considered that the implementers did not favor local communities.